Development and content validity testing of patient-reported outcome (PRO) items to assess chest congestion associated with the common cold for use in children and adolescents - Rob Arbuckle; Chris Marshall; Laura Grant; Kate Burrows; Helmut H. Albrecht; Tim Shea (SpringerOpen, 2022)
Abstract Background This article describes qualitative interviews conducted with children (aged 6-11), adolescents (aged 12-17), and adults with the common cold as well as parents/caregivers of the 6-8-year-old children. The aim was to support the refinement and content validity testing of patient-reported outcome (PRO) items assessing chest congestion that could be used as pediatric clinical trial endpoints. Feasibility and acceptability of administering the PRO items electronically on a hand-held touch-screen device were also evaluated. The sample included children aged 6-8 years (n = 14), 9-11 years (n = 13), adolescents aged 12-17 years (n = 12), and adults (n = 10), all of who had current (n = 38) or recent (n = 11) cold. Both concept elicitation (CE) and cognitive debriefing (CD) interviews were conducted with all of these participants, conducted over in two rounds. Ten parents/caregivers of participants aged 6-8 years were also interviewed (separately from their child) regarding how they thought their children would understand the items. The CE interviews explored the qualitative experience of having chest congestion and related symptoms of the common cold. Following their CE interview, participants completed draft items on an electronic patient-reported outcome (ePRO) device twice daily for 2-5 days prior to their CD interview. During the CD interview participants were asked about relevance, understanding and interpretation of the draft PRO items. Qualitative analysis of the interview data and descriptive analyses of the ePRO data were conducted following both rounds of interviews, with modifications to the items implemented following Round 1 and tested in Round 2. Results Eight symptoms were reported by children during concept elicitation. Findings from the child, adolescent, and adult/parent interviews supported revisions to the items and enabled the selection of the best performing items. The results provided evidence that the final items were well understood by participants and relevant to their experiences of chest congestion as part of a common cold. Findings also provide support for using the same items across age groups. Conclusions The results of the CE and CD interviews provide evidence supporting the content validity of new PRO items assessing the experience of chest congestion symptoms associated with common cold experienced by children, adolescents, and adults.